Cultural Complexity Thinking by Social Workers in Their Address of Sustainable Development Goals in a Culturally Diverse South Africa. Issue 2 (3rd May 2020) - Zimba, Zibonele France
ABSTRACT: The global agenda of Sustainable Development Goals (SDGs) provides social workers an opportunity to redefine their contributions pertaining to socioeconomic development, human rights and the environment. This is specifically so for social workers in South Africa, whose contributions have been narrowed. Therefore, this paper identifies potential contributions by social workers in relation to the SDGs using cultural complexity thinking in a diverse country. The paper also points out difficulties faced by social workers on their contribution in the SDGs in a culturally diverse South Africa. The paper concludes that social workers must stand alongside their service users as partners in contributing to justice and equality by achieving the SDGs.